Associations among circulating colony-stimulating factor-1, estrogen, and bone mineral density in postmenopausal women: results from a randomized placebo-controlled trial. Issue 2 (February 2018) - Haas, Andrea V.; Cong, Elaine; Simpson, Christine A.; Sukumar, Nitin; Deng, Yanhong; Insogna, Karl L.
Abstract: Objective: This study addresses the relationship between circulating levels of colony-stimulating factor 1 (CSF-1) and rates of postmenopausal bone loss. The purpose was to test the hypothesis that CSF-1 levels would correlate with the rate of bone loss in estrogen-deficient woman. We further hypothesized that estrogen replacement would eliminate this association. Methods: This was an ancillary study to the parent Kronos Early Estrogen Prevention Study (KEEPS)—a 4-year randomized placebo-controlled study that evaluated the effects of estrogen therapy on cardiovascular endpoints. Women between of the ages of 42 and 58, who had been amenorrheic for ≥6 months and ⩽36 months, were enrolled in KEEPS. Participants were randomized to conjugated equine estrogen 0.45 mg daily, transdermal estradiol 50 micrograms weekly, or placebo. Results: There was no correlation between serum levels of CSF-1 and bone mineral density at the spine, hip, or femoral neck in estrogen-deficient women (correlation 0.0017, P  = 0.99 for spine; correlation 0.0010, P  = 0.0079 for hip, and correlation 0.0019, P  = 0.99 for femoral neck). There was also no significant correlation in the treatment group (correlation 0.0015, P  = 0.99; correlation −0.00024, P  = 0.99; correlation 0.0011, P  = 0.99 at spine, hip, and femoral neck respectively). Conclusions: This study did not demonstrate a meaningful relationship between circulating levels of CSF-1 and bone mineral density in either the placebo group or estrogen-treated group. Although CSF-1 is required for osteoclastic bone resorption, our data suggest that circulating levels of the cytokine may not reflect this process.